2011
DOI: 10.1118/1.3646756
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast density measured on MR images acquired using fat‐suppressed versus nonfat‐suppressed sequences

Abstract: Purpose: To investigate the difference of MR percent breast density measured from fat-suppressed versus nonfat-suppressed imaging sequences. Methods: Breast magnetic resonance imaging (MRI) with and without fat suppression was acquired from 38 subjects. Breasts were divided into subgroups of different morphological patterns ("central" and "intermingled" types). Breast volume, fibroglandular tissue volume, and percent density were measured. The results were compared using nonparametric statistical tests and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…The study also showed (78) that the MGD from FFDM and DBT for a single view increased with increasing breast thickness and was used to construct the plots for 50% and 14.3% fibroglandular breasts in Figure 2a. A 50% fibroglandular breast corresponds to the assumed average breast composition used in United States protocol and a 14.3% fibroglandular breast corresponds to approximately average realistic composition reported in recent studies (79)(80)(81)(82). It is relevant to note that the estimated MGD is with automatic exposure control, and for the desired image quality, the technique factors and consequently the MGD can be chosen.…”
Section: Radiation Dosementioning
confidence: 99%
“…The study also showed (78) that the MGD from FFDM and DBT for a single view increased with increasing breast thickness and was used to construct the plots for 50% and 14.3% fibroglandular breasts in Figure 2a. A 50% fibroglandular breast corresponds to the assumed average breast composition used in United States protocol and a 14.3% fibroglandular breast corresponds to approximately average realistic composition reported in recent studies (79)(80)(81)(82). It is relevant to note that the estimated MGD is with automatic exposure control, and for the desired image quality, the technique factors and consequently the MGD can be chosen.…”
Section: Radiation Dosementioning
confidence: 99%
“…In the next step, a horizontal truncation line is delineated through the point placed 15 mm below point n , which places it on the anterior boundary of the sternum in the edge map image (Figure 4b). Based on Change's work [32] and the advice of two experienced radiologists, a separation threshold of 15 mm is selected.…”
Section: Detection Of Approximated Breast Boundarymentioning
confidence: 99%
“…10 Kopans 11 advocated for the use of threedimensional (3D) imaging for estimating the amount of dense tissue present in the breast. Techniques for quantitative estimation of fibroglandular tissue volume, and consequently the ratio of fibroglandular tissue volume to the total breast volume, often referred to as "volumetric glandular fraction" (VGF) using 3D imaging techniques such as breast MRI, 12,13 dedicated breast CT, 14,15 and ultrasound tomography 16 have been developed.…”
Section: Introductionmentioning
confidence: 99%